Institutional Approach in Economics and Institutional Economic Thinking - Devy C Yudihutomo (Penerbit Hellow Pustaka, 2024)
Aspects of economic methodology contained in Institutional economics are often incorporated into orthodox economics. Orthodox economics means economic thoughts that use and continue classical economic views, such as free competition, perfect competition, consumer satisfaction. The person who was most influential and had a dominant role in the existence of the Institutional school was Thorstein Bunde Veblen. He criticized Classical and Neo-classical economic theories which ignored non-economic aspects such as institutions and the environment. In fact, Veblen considered that the influence of circumstances and the environment was very large on people's economic behavior. Unsupportive political and social structures can cause distortions in economic processes. For Veblen, society is an evolutionary phenomenon, everything is constantly changing. A person's behavioral patterns in society are adapted to current social conditions. If the behavior is suitable and accepted, then the behavior will continue. On the other hand, if a behavior is deemed unsuitable, the behavior will be adapted to the environment. These circumstances and environments are what Veblen called